Glycol methacrylate (GMA) embedding for light microscopy. II. Immunohistochemical analysis of semithin sections of undecalcified marrow cores. Issue 8 (August 1988) - Islam, A; Archimbaud, E; Henderson, E S; Han, T
Abstract : A routine method allows bone marrow biopsy specimens to be embedded in glycol methacrylate (GMA), a water miscible plastic, and to benefit from the advantages of good morphology with immunoperoxidase detection of a wide range of cellular antigens useful in diagnosing and classifying various haematopoietic disorders. Marrow cores were fixed in cold Bouin's solution, rinsed in cold phosphate buffer, dehydrated in cold methanol, infiltrated and embedded in cold GMA, then polymerised at 4 degrees C. Sections were cut at 2 micron thickness with a Tungsten carbide knife in a Jung's high performance microtome (Autocut). Antigenecity was preserved when drying slides at room temperature but pronase digestion was necessary to re-expose the antigens in bone marrow biopsy sections embedded in GMA. Histostik, a new adhesive, was used to coat the glass slides to prevent section loss during enzyme digestion and immunostaining procedures. This method of adapting plastic embedding to undecalcified marrow cores preserves marrow architecture and cellular details and it can serve as a useful adjunct to analyse the bone marrow from patients with myeloproliferative and lymphoproliferative disorders. This technique may also be applicable in non-haematological malignant conditions which affect the marrow.